2019
DOI: 10.21203/rs.2.19171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Plasmodium vivax outbreak to elimination: lessons learnt from a retrospective analysis of data from Guantang

Abstract: Background: Malaria was once a serious public health problem in China with Plasmodium vivax the major species responsible for more than 90% of local transmission. Following significant integrated malaria control and elimination programs, malaria burden declined, and by 2017 China recorded no indigenous cases. To understand the historical malaria transmission patterns and epidemic characteristics in China and insights useful to guide P. vivax malaria control and elimination elsewhere, a retrospective study was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Other malaria vectors, such as An. sinensis , are preferentially zoophilic, 50 with an averaged preference ratio of 1:11.93 between humans and cattle 51 . Our results showed that Pipiserpin may be used to vaccinate animals to generate antisera, which would then be ingested when mosquitoes feed on these animals.…”
Section: Discussionmentioning
confidence: 77%
“…Other malaria vectors, such as An. sinensis , are preferentially zoophilic, 50 with an averaged preference ratio of 1:11.93 between humans and cattle 51 . Our results showed that Pipiserpin may be used to vaccinate animals to generate antisera, which would then be ingested when mosquitoes feed on these animals.…”
Section: Discussionmentioning
confidence: 77%